ARNTL2 is a Prognostic Biomarker and Correlates with Immune Cell Infiltration in Triple-Negative Breast Cancer - Wang X; Li Y; Fu J; Zhou K; Wang T (Dove Medical Press, 2021)
Xiaoyu Wang,1 Yan Li,2 Jianchang Fu,3 Kewen Zhou,1 Tinghuai Wang1 1Department of Physiology, Zhongshan School of Medicine, Sun Yat-sen University, Guangzhou, 510080, People's Republic of China; 2Department of Pathology, The First Affiliated Hospital of Sun Yat-sen University, Guangzhou, 510080, People's Republic of China; 3Department of Pathology, Sun Yat-sen University Cancer Center, Guangzhou, 510060, People's Republic of ChinaCorrespondence: Tinghuai Wang; Kewen ZhouDepartment of Physiology, Zhongshan School of Medicine, Sun Yat-sen University, Guangzhou, 510080, People's Republic of ChinaEmail wangth@mail.sysu.edu.cn; zhoukw6@mail.sysu.edu.cnBackground: Triple-negative breast cancer (TNBC) is the most aggressive breast cancer subtype and is associated with poor prognosis. The aberrant expression of circadian genes contributes to the origin and progression of breast cancer. The present study was designed to explore the potential function and prognosis value of circadian genes in TNBC.Methods: The transcriptome data of circadian genes were downloaded from The Cancer Genomic Atlas (TCGA), GSE25066 and GSE31448 datasets. The differential expressed circadian genes between non-TNBC and TNBC patients were analysed by Wilcoxon test. Univariate and multivariate Cox regression analyses were employed to identify the prognostic circadian genes. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Set Enrichment Analysis (GSEA) were performed to study the biological functions of ARNTL2. The composition of 22 immune cells in the tumour samples was estimated with CIBERSORT algorithm. The correlations between ARNTL2 expression and tumour-infiltrating immune cells were evaluated by Spearman correlation coefficient.Results: A total of 8 circadian genes were found to be differentially expressed between non-TNBC and TNBC, but only ARNTL2 has prognostic value. Multivariate Cox analysis identified that ARNTL2 was an independent prognosis factor for overall survival and relapse-free survival in TNBC patients. Functionally, ARNTL2 was mainly involved in immune response processes such as positive regulation of cytokine production, regulation of innate immune response, and cellular responses to molecules of bacterial origin. High expression of ARNTL2 was positively correlated with activated CD4 memory T cells, activated mast cells, and neutrophil infiltration and the expression of markers of neutrophils (ITGAM), dendritic cells (HLA-DRA, HLA-DPA1, ITGAM), Th1 (IL1B, STAT1), Th2 (IL13), Th17 (STAT3) and mast cells (TPSB2, TPSAB1).Conclusion: ARNTL2 may be linked with the functional modulation of the tumour immune microenvironment and serve as a potential biomarker for predicting the prognosis of TNBC patients.Keywords: ARNTL2, immune cell infiltration, triple-negative breast cancer, biomarker, circadian rhythm